Shallow water sponges that associated to mangrove ecosystem at Labuhan conservation area in Sepulu, Bangkalan, Madura, East Java Province - Edwin Setiawan; Farid Kamal Muzaki; Nova Maulidina Ashuri (Department of Biology, Faculty of Sciences and Mathematics, Universitas Diponegoro, 2018)
Sponges (Porifera) are benthic sessile animals that have an important role in coastal ecosystems. Mangrove habitat is an example of a coastal ecosystem that can be inhabited by sponges. Research diversity on shallow water sponges in mangrove areas in Indonesia or even large scale such as the Indo-Pacific area are still relatively underestimated because of an extreme difference tidal factors. For this reason, we aimed to research a diversity of shallow water sponges in mangrove Indonesia, especially in East Java Province to enrich and inform additional data on its biodiversity. Research on shallow water sponges in mangrove was conducted from June 2017 to January 2018 at two stations located on the coast of Labuhan Village, Sepulu District, Bangkalan Regency, Madura - East Java. Mangrove areas are consisted of Sonneratiaarea in the west (B) and Rhizophoramangroves in the east (R). There were six sponge genera identified, namely Spongia, Dysisdea, Lendelfedia, Dactylospongia, Cynachyrellaand one unidentified genus. Sonneratiamangrove was inhabited by of five genera sponges, whereas Rhizoporamangrove was inhabited only by one genus